Metodologi Design Science Research Dalam Pengembangan Sistem Informasi Tata Naskah: Design Science Research Methodology In Development of a Manuscript Information System - Ratna Juita (Universitas Papua, 2018)
Information Technology and Communication, since its massive development decadesago has brought a new paradigm of how the works can be completed. InformationSystem among its developments brings a new hope how the works can be effective andefficient. In this research, an archieve Information Sytem is developed as a mean tohelp a government office, Kantor Kepegawaian Negara Regional XIV, to manage all thecivil servants in West Papua Province. In particular, this Information System aims toease the government boars in that particular matter to store and retrieve as well astrace all the civil servants in regards their mutation, activation, reteriment, etc. Thiscould be the issue as there are thousand of them and deployed in all area in thatprovince. With the help of a Design Science Resaerch methodology in InformationSystem, this research successfully demonstrated the development and the evaluation ofworkd product.